IMPLEMENTASI SANGGUL UKEL TEKUK SEBAGAI SANGGUL JAWA - Vony Fatmawati Hipij; Sulistyami Sulistyami (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
This research aims to see the results of ukel tekuk implementation. The design in this study using one shot case study with research subject of university student Adi Buana force of 2017 which amounted to 35 people. The research method used is a performance test to make buck ukel buckling. The conclusions of this study found that bun buckling uk is widely used by royal families, permasuri, princesses, host or caregiver and followed by the surrounding community. Keywords: ukel tekuk style, one shot case study, performance test.